Open source software adoption for academic libraries - Saleh Al Zeheimi, Saleh Sulaiman; Zeki, Akram M.; Mohamed Razi, Mohamed Jalaldeen (IIUM Press, International Islamic University Malaysia, 2017)
This study aims to explore the main factors facilitating or inhibiting the adoption of OSS in academic libraries. It also focuses on the decisions that IT managers make about OSS adoption. This study contributes different from previous studies in the terms of: (1) the samples was collected from the Omani libraries; (2) the research framework is developed based on technology adoption theory attributes and; (3) it uses a multi-method approach that provides an opportunity to triangulate the study’s results. The multi-method approach had increase the reliability of the findings by triangulating the results with theory and literature. This research has contributed to knowledge by adding new factors that influence technology adoption. Based on the findings of this research, OSS has been identified as a viable alternative to proprietary software for academic libraries in Oman